Pengaruh Model Pembelajaran PjBL-STEM Terhadap Kemandirian Belajar Siswa Pada Materi Sistem Peredaran Darah - Nurillah, Nurillah; El Islami, R. Ahmad Zaky; Biru, Lulu Tunjung (UNIB Press, 2025)
Low learning independence is a challenge in science learning. The right learning model, such as PJBL-STEM, can be an alternative for students' understanding of the material in depth. This study was conducted to determine the influence of the PjBL-STEM learning model on students' independence in learning the circulatory system material. The method used is a quasi-experiment with a pretest-posttest control group design, involving two classes, namely, the experimental class and the control class. This research instrument includes a learning independence questionnaire and an observation sheet on learning implementation. The results of the research that have been carried out show that the PjBL-STEM learning model has an influence on student independence in learning. The data was analyzed through IBM SPSS version 26. The results of this hypothesis test show that the PjBL-STEM model significantly increases student independence in learning, obtaining a significance value (2-tailed) of 0.022 < 0.05, thus H0 is rejected and H1 is accepted, which corroborates that the PjBL-STEM model has a significant effect on increasing student learning independence in circulatory system materials.